Molecular and clinical determinants of response and resistance to rucaparib for recurrent ovarian cancer treatment in ARIEL2 (Parts 1 and 2) - Elizabeth M. Swisher (Nature Portfolio, 2021)
The identification of biomarkers of response to PARP inhibitors can enable selection of appropriate ovarian cancer patients for treatment. In this study, the authors report clinical results and exploratory biomarker analyses from the ARIEL2 phase 2 clinical trial on the safety and efficacy of the PARP inhibitor rucaparib in patients with recurrent ovarian cancers